2007
DOI: 10.2527/jas.2006-366
|View full text |Cite
|
Sign up to set email alerts
|

Breed-associated variations in the sequence of the pig 3β-hydroxysteroid dehydrogenase gene1

Abstract: The entire sequence of the pig 3beta-hy-droxysteroid dehydrogenase (3beta-HSD) gene has recently become known. This gene is deemed to be important in androstenone metabolism in pig liver, and its defective expression has been shown to be related to androstenone accumulation in adipose tissue and the development of boar taint. The aim of the present work was to do the following: 1) define the structure of the pig 3beta-HSD gene and 2) compare 3beta-HSD DNA sequences from pigs of different breeds, which vary in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…Furthermore, no differences in allele expression were observed, as well as none significant associations with any of the SNPs investigated (Table 4). The association results are in concordance with a recent study by Cue et al [45], obtaining no significant associations between the HSD3B SNPs, all located in the 5'UTR, and the androstenone level in fat from several breeds.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, no differences in allele expression were observed, as well as none significant associations with any of the SNPs investigated (Table 4). The association results are in concordance with a recent study by Cue et al [45], obtaining no significant associations between the HSD3B SNPs, all located in the 5'UTR, and the androstenone level in fat from several breeds.…”
Section: Discussionsupporting
confidence: 92%
“…Tajet et al [5]), sequence variation, mRNA and protein levels have been found in several studies [43-45]. In this study we found breed differences in level of expression for the genes CYP19A2 , PGRMC1 and CYP21.…”
Section: Discussionsupporting
confidence: 71%
“…The HSD3B gene has been entirely sequenced including the promoter. Variations detected in the promoter sequences of the porcine HSD3B do not show any relationship with the level of androstenone in fat, but are breed-dependent [10]. It can be speculated that transcription factors responsible for the liver-specific regulation of the expression of HSD3B may play an important role in regulating the deposition of androstenone in pig adipose tissue.…”
Section: Genes Involved In the Degradation Of Androstenonementioning
confidence: 93%
“…The gene has been mapped to the chromosome 4q16–4q21 [29]. The structure of the porcine 3β-HSD gene was described by Cue et al [72]. The protein encoded by the porcine gene displays most similarity to human 3β-HSD type I (373 aa) and murine types I, II, II and IV.…”
Section: 3β-hsd Isoforms In the Livermentioning
confidence: 99%
“…The enzymes responsible for the Phase I metabolism of skatole are to a great extent regulated by the presence of androstenone [113119]. Cue et al [72] detected a number of polymorphisms in the porcine 3β-HSD 5′-flanking region. However, none of these has been associated with variations in androstenone levels.…”
Section: The Boar Taint Phenomenonmentioning
confidence: 99%